2010
DOI: 10.1007/s11096-010-9396-7
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of use of emergency oral contraception among Portuguese women

Abstract: Emergency oral contraception was used correctly by 96.9% of user-purchasers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
2
5
0
1
Order By: Relevance
“…22 The importance to counsel adolescents about ongoing contraceptive measures and sexually transmitted infections have been highlighted in other studies; it was particularly important to cover these aspects in scenario 1. 11,39 However, staff at four of the 12 pharmacies presented with this scenario provided moderate patient counselling (two of which supplied the ECP) and the remaining eight pharmacies provided no counselling. Although ten of the pharmacies refused to supply the ECP, thereby to some extent negating the need for the provision of detailed advice about the use of the ECP, these staff missed an opportunity to provide information about additional aspects such as the risk of contracting sexually transmitted diseases during unprotected intercourse and ongoing contraceptive measures.…”
Section: Overall Management Of Ecp Requestsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 The importance to counsel adolescents about ongoing contraceptive measures and sexually transmitted infections have been highlighted in other studies; it was particularly important to cover these aspects in scenario 1. 11,39 However, staff at four of the 12 pharmacies presented with this scenario provided moderate patient counselling (two of which supplied the ECP) and the remaining eight pharmacies provided no counselling. Although ten of the pharmacies refused to supply the ECP, thereby to some extent negating the need for the provision of detailed advice about the use of the ECP, these staff missed an opportunity to provide information about additional aspects such as the risk of contracting sexually transmitted diseases during unprotected intercourse and ongoing contraceptive measures.…”
Section: Overall Management Of Ecp Requestsmentioning
confidence: 99%
“…[8][9][10] Research has also indicated that the nonprescription use of the ECP is appropriate in that it is only used as an emergency measure when there was failure of another contraceptive method, such as a condom. 11 The over the counter availability of the ECP does not seem to lead to increased use, an increase in unprotected sex or a decrease in the use of more reliable methods of contraception. 8,[11][12] However, a recent Australian telephone survey of a random sample of 632 women aged between 16-35 years indicated that less than half of the women were aware of it being available without a prescription, and the researchers subsequently recommended that a media campaign be implemented to promote its availability from pharmacies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results coincide with those of similar studies [ 17 , 18 ]. Fontes [ 19 ] concludes that because EC is used correctly in 96.9% of users/buyers, knowledge regarding this medication may be considered as already sufficiently attained.…”
Section: Discussionmentioning
confidence: 99%
“…No Estado de Pernambuco, em uma pesquisa realizada com 4.210 adolescentes de 14 a 19 anos de idade, Araújo e Costa (2009) encontraram uma proporção de uso anterior de AE da ordem de (Rocca et al, 2007), Portugal (Fontes et al, 2010) e Itália (Tafuri et al, 2012), também encontraram como principal razão para usar a AE, as falhas no uso de MAC regular, como a ruptura do preservativo.…”
Section: Anticoncepção De Emergênciaunclassified